Mística, necessidade e lógica (Mystic, necessity and logic) - DOI: 10.5752/P.2175-5841.2012v10n28p1380 - Jourdan, Camila Rodrigues (Horizonte, 2012)
This paper clarifies the extent to which Logic, in the usual sense (and even naïve) of the term, as composed of the correct thinking’s necessary laws, can be understood as Mystic. This seems strange, because the Mystic is usually understood as an experience of overcoming the dualities, where rational thinking collapses and finds its limit. On the other hand, the logic is understood as the paradigm of rational thinking. It is argued that the most general laws of reason and speech are related to Mystic in the sense that the foundation of the reason is equated to its limit. The language lies thus with the silence and the laws and justifications no longer operate as such. We conclude that the adherence necessary that accompanies the collapse of meaning and truth value of certain linguistic utterances is what we call mystical experience. It is about an experience to which we are led by the workings of our linguistics meaning, establishing what is meant by religious experience.